GAMIFICATION AS ONE OF THE CURRENT TRENDS IN OPTIMIZING THE EDUCATIONAL PROCESS IN THE TRAINING OF PHARMACY SPECIALISTS - Matushchak , M.; Zakharchuk , O.; Horoshko , O.; Sakhatska , I.; Ezhned , M.; Kostyshyn , L. (Collection of scientific papers «ΛΌГOΣ», 2022)
Higher education experiences the challenges of time, it requires the training of specialists of a high professional level, at the same time, the learning process is characterized by time limitations and a significant burden on those seeking education [1]. All these factors are particularly relevant to pharmaceutical education, as there are quite high requirements for the professional qualities of employees in the pharmaceutical industry. The question arises as to how, in the conditions of a limited time resource, to conduct professional training in the most effective way to acquire the necessary competencies for students of higher education. Of course, this requires the use of scientifically based methodological approaches to solve today's challenges. An interesting issue is the prospects for introducing gamification into the educational process of pharmacy specialists.